LA EXPEDICION DEL M N GRACIOSO POR AGUAS DEL EXTREMO NOROESTE MEXICANO I RESUMEN GENERAL - OSORIO TAFALL, B F (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Following a brief history of the discoveries pertaining to malaria and the malarial organism, there are brief sections on the spp of Plasmodium, bird, mammalian, and reptilian plasmodia, life cycles, types of vector mosquitoes, attempts to culture the or
AN ESC NAC CIENC BIOL
Keywords: EXPEDICION, M N GRACIOSO, AGUAS, EXTREMO NOROESTE MEXICANO, RESUMEN GENERAL; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL